2009
DOI: 10.1016/j.atherosclerosis.2008.03.023
|View full text |Cite
|
Sign up to set email alerts
|

γ-Glutamyltransferase activity in human atherosclerotic plaques—Biochemical similarities with the circulating enzyme

Abstract: The results obtained suggest the presence in plaques of a serum-like GGT protein, indicating that a direct contribution of serum GGT to enzyme activity found within atherosclerotic lesions is possible. Data also indicate the occurrence of GGT-mediated redox reactions within plaque environment, which might influence plaque progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
111
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(124 citation statements)
references
References 40 publications
5
111
0
1
Order By: Relevance
“…This GGT-induced LDL oxidation may be a possible underlying mechanism of atherosclerotic progression 13) . The study by Franzini et al also demonstrated a positive correlation between the serum GGT level and GGT activity in atherosclerotic plaques 31) . Our results showing an elevated serum GGT level to be associated with carotid plaque are in agreement with the above findings, and this association supports the concept of the presumptive pathological mechanism of atherosclerosis.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…This GGT-induced LDL oxidation may be a possible underlying mechanism of atherosclerotic progression 13) . The study by Franzini et al also demonstrated a positive correlation between the serum GGT level and GGT activity in atherosclerotic plaques 31) . Our results showing an elevated serum GGT level to be associated with carotid plaque are in agreement with the above findings, and this association supports the concept of the presumptive pathological mechanism of atherosclerosis.…”
Section: Discussionmentioning
confidence: 88%
“…glutathione, cysteinyl-glycine, cysteine and LDL/GGT complexes 31) . Cysteinyl-glycine, a dipeptide derived from GGT-mediated glutathione degradation, promotes LDL oxidation via an iron reduction reaction that results in the production of superoxide radicals.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][25][26][27] Several mechanisms have been postulated for these associations and these include the pro-inflammatory and pro-oxidant activities of GGT [11], as well as its direct involvement in atheromatous plaque formation. [28,29] Though the pathogenesis of dementia has not been completely elucidated, mechanistic research provides strong support for inflammatory and oxidative processes. [3,4,30] Our results are therefore biologically plausible as GGT mediates these processes.…”
Section: Possible Explanations For Findingsmentioning
confidence: 99%
“…5 GGT is the only extracelullar enzyme responsible for the catabolism of reduced glutathione. 6 There is evidence of GGT ability to catalyse GSH-dependent lipid peroxidation in the presence of Fe 3þ .…”
Section: Introductionmentioning
confidence: 99%